Risk and Protective Factors for Difficulty Controlling Violent Behavior in National Guard and Reserve Service Members. Issue 3 (February 2021) - Worthen, Miranda; Rathod, Sujit D.; Cohen, Gregory; Sampson, Laura; Ursano, Robert; Gifford, Robert; Fullerton, Carol; Galea, Sandro; Ahern, Jennifer
Violent behavior is an important problem for military service members and veterans. A representative cohort of U.S. Reserve and National Guard personnel ( N = 1, 293) were interviewed to assess self-reported problems controlling violent behavior, deployment traumas, posttraumatic stress disorder (PTSD), alcohol abuse, and social support. Poisson regression models were used to estimate the associations of violent behavior with risk and protective factors. Problems controlling violent behavior were uncommon among male (3.3%) and female (1.7%) service members. Adjusted prevalence ratios (aPR) showed associations between violent behavior and deployment traumas (aPR = 1.67, 95% confidence interval [CI] = [1.34, 2.08]), PTSD (aPR = 9.95, 95% CI = [5.09, 19.48]), and PTSD symptom severity (aPR for each additional PTSD symptom = 1.07, 95% CI = [1.06, 1.09]). Social support was associated with lower prevalence of violent behavior (aPR = 0.62, 95% CI = [0.52, 0.76]). The association between violent behavior and alcohol abuse was not statistically significant (aPR = 1.94, 95% CI = [0.92, 4.09]). Results were consistent when the population was restricted to personnel who had deployed to a war zone. Problems controlling violent behavior were less common in this cohort than has been documented in other studies. Associations of violent behavior with risk and protective factors are consistent with prior research.